1999
DOI: 10.1046/j.1365-2672.1999.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on strong and weak killer phenotypes of wine yeasts: production, activity of toxin in must, and its effect in mixed culture fermentation

Abstract: R .A . M U SM AN N O, T. D I M AG G IO AN D G. CO R AT ZA . 1999. Two different killer phenotypes were detected among K ¦ (killer) yeasts isolated from spontaneous wine fermentations using a plate bioassay. The two phenotypes differed in their degree of killer activity, and were designated as SK ¦ (strong killer) and WK ¦ (weak killer). Strains showing either phenotype were assayed for expression of killer activity under different growth conditions. Growth in must negatively affected expression of the killer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The most extreme amensalism described is the killer phenomenon, discovered 50 years ago (Bevan & Makover, 1963): the production of specific extracellular proteins and glycoproteins by certain yeast strains (killer yeasts) that kill other strains (sensitive yeasts). There is an extensive literature describing this phenomenon for S. cerevisiae strains and detailing the nature of these proteins (Young, 1987;van Vuuren & Jacobs, 1992;Shimizu, 1993;Musmanno et al, 1999;Gutierrez et al, 2001). The killer phenomenon contributes to the succession of different yeast strains during fermentation.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…The most extreme amensalism described is the killer phenomenon, discovered 50 years ago (Bevan & Makover, 1963): the production of specific extracellular proteins and glycoproteins by certain yeast strains (killer yeasts) that kill other strains (sensitive yeasts). There is an extensive literature describing this phenomenon for S. cerevisiae strains and detailing the nature of these proteins (Young, 1987;van Vuuren & Jacobs, 1992;Shimizu, 1993;Musmanno et al, 1999;Gutierrez et al, 2001). The killer phenomenon contributes to the succession of different yeast strains during fermentation.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Killer toxins appear to represent an interesting solution as antimicrobial agents, for the partial or complete substitution of the use of chemical agents. Screening to determine the occurrence of killer yeasts in winemaking environments has formed part of several studies, and these have shown the widespread presence of killer and neutral phenotypes in wines, and on cellar surfaces and winery equipment, while the sensitive yeasts were recovered only occasionally ; Musmanno et al 1999).…”
Section: Non-saccharomyces Yeasts In the Control Of Undesirable Yeastsmentioning
confidence: 99%
“…1), there were differences in the diameter of the clear zone of growth inhibition around the colonies of the killer strains. This phenomenon has first been reported for killer isolates of S. cerevisiae in spontaneous wine fermentations from the Tuscany region of Italy (Musmanno et al 1999) and may be due to the production of different amounts of toxin. According to this report we divided also the killer isolates into two groups named, respectively, as strong killer (SK) or weak killer (WK) phenotypes.…”
Section: Resultsmentioning
confidence: 92%
“…The magnitude of the killer effect may depend on the ratio of killer to sensitive strains (Heard and Fleet 1987), on the presence of protective neutral yeasts (Da Silva 1996) or on the occurrence of strong and weak killer phenotypes in wine yeasts (Musmanno et al 1999).…”
Section: Introductionmentioning
confidence: 99%